Representing Bodies. Victor Brauner’s Hybrids, Fragments and Mechanisms - Cărăbaş, Irina (Nordlit, 2007)
The Romanian avant-garde looked for inspiration in two principal places where artists from all-over Europe gathered, confronted and discussed their ideas of a new art. While Berlin nourished the constructivist orientation of the Romanian avantgarde, Paris stimulated its interest in surrealism. Although Berlin was by far more significant as a stimulus for the synthesis of all arts and all modern movements toward which the Romanian avant-garde strove, Paris had the advantage of an emotional attachment. The French culture had been set long ago as a model for the entire Romanian modern culture and institutions. Consequently it is not surprising that poets and artists, including Victor Brauner, chosed to live and work in Paris in order to feel closer to what was considered to be the origin. Victor Brauner is discussed both in the context of the Romanian avant-garde and in the history of the French surrealism, but one cannot detect any tension between center and periphery. One motivation can be found in the myth he creates for himself. Meanwhile it is obvious that he wanted to identify himself with the French surrealism. Once settled in France he paid great attention to the theories and to the artists André Breton promoted. I will discuss the myth of the artist as well as the threads which connect Brauner to other artistic strategies bringing forth the body problem. Almost always his paintings and drawings display the ineluctable presence of a metamorphic body within no narrative construction. This preoccupation informed every stage of his career as he dedicated it the greatest energies of his artistic inventiveness. Before going into the subject, one needs to frame Brauner in a larger picture.